Characterizing the plant functional traits of coffee agroecosystems in Indonesia - Satriawan, Tin W.; Luo, Xiangzhong; Yu, Liyao; Ramdhania, Shafira Nur; Syahid, Luri Nurlaila; van Noordwijk, Meine; Hairiah, Kurniatun; Sari, Rika Ratna; Sulistyawati, Endah; Lupascu, Massimo; Budianti, Noviana (Frontiers in Plant Science, 2026)
Indonesia, the world’s third-largest coffee producer, is rapidly expanding coffee agroecosystems, often at the expense of deforestation. Understanding the ecophysiology of coffee agroecosystems is thus critical for assessing their impacts on the regional carbon cycle. However, current knowledge of coffee ecophysiology is largely derived from studies in Central and South America and equatorial Africa, with few observations from Indonesia despite its distinct climatic context and large area. In this study, we measured plant functional traits (i.e., leaf structural, physiological, and chemical traits) of coffee plants at four distinct sites in Java, Indonesia, to assess the spatio-temporal variations of coffee leaf traits along with their relationship with shade and reproductive output. We found that physiological traits showed the largest within-site variation, while structural traits varied most strongly among sites. Across seasons, photosynthetic traits (i.e., light-saturated photosynthetic rate Amax and maximum carboxylation rate Vcmax) exhibited pronounced seasonality at a robusta (C. canephora) coffee site, whereas arabica coffee (C. arabica) and hybrid (C. arabica x C. canephora) sites showed greater seasonal shifts in structural traits. We also found that denser shade promoted resource-acquisitive strategies (higher photosynthetic capacity, lower leaf mass per area), but this did not translate into greater fruit production. Our study provides one of the first field-based assessments of the ecophysiology of coffee agroecosystems in Indonesia, which will advance our understanding of coffee expansion on the regional carbon cycle.